PENGARUH INTELLECTUAL CAPITAL DAN RISK BASED CAPITAL (RBC) TERHADAP KESEHATAN KEUANGAN PERUSAHAAN PT. CHUBB LIFE INSURANCE MEDAN - Nst, Nurul Hafizah; Kusmilawaty, Kusmilawaty; Rahmani, Nur Ahmadi Bi (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to determine the influence of Intellectual Capital and Risk Based Capital on Financial Health at PT. Chubb Life Insurance Medan branch. The type of research used is quantitative research. The data used in this research is secondary data obtained from financial reports in the 2020-2022 period. The data analysis techniques used in this research are classical assumption test analysis (including normality test and multicollinearity test), coefficient of determination, multiple linear regression test, T test and F test. The results of the research show that Intellectual Capital which consists of Value Added Capital Employed ( VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA) have a positive influence on the company's financial health with respective values of 0.023, 0.042, and 0.012 which are smaller than the significant value of 0.05. Partially, RBC also has a positive effect on financial health with a value of 0.022 < 0.05. The results of this research also show that Intellectual Capital and Risk Based Capital simultaneously influence Financial Health which can be seen with a significance value of 0.000 < 0.05.